2021
DOI: 10.15585/mmwr.mm7005a1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Disparities in Risk Factors for Adverse COVID-19–Related Outcomes, by Race/Ethnicity — Behavioral Risk Factor Surveillance System, United States, 2017–2019

Abstract: Sexual minority persons experience health disparities associated with sexual stigma and discrimination and have a high prevalence of several health conditions that have been associated with severe coronavirus disease 2019 (COVID-19) (1,2). Current COVID-19 surveillance systems do not capture information about sexual orientation. To begin bridging the gap in knowledge about COVID-19 risk among sexual minority adults, CDC examined disparities between sexual minority and heterosexual adults in the prevalence of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 6 publications
1
71
0
Order By: Relevance
“…Sexual minority individuals are less likely to seek health care due to stigma and discrimination [ 31 ]. Furthermore, compared with heterosexual individuals, the COVID-19 pandemic disproportionately impacted mental health [ 32 ] and economic capability [ 33 ] of sexual minority individuals and thus may compromise their ability to access health care services. A recent study reported that the COVID-19 pandemic resulted in interruptions of HIV treatment in sexual minority individuals [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual minority individuals are less likely to seek health care due to stigma and discrimination [ 31 ]. Furthermore, compared with heterosexual individuals, the COVID-19 pandemic disproportionately impacted mental health [ 32 ] and economic capability [ 33 ] of sexual minority individuals and thus may compromise their ability to access health care services. A recent study reported that the COVID-19 pandemic resulted in interruptions of HIV treatment in sexual minority individuals [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been no other estimates published in the world on the incidence, hospitalization, or death rates in sexual and gender minority populations. A number of countries have been calling for this data, for example, in the US, where it is known that sexual minority individuals have a higher self-reported prevalence of several underlying health conditions associated with severe outcomes from COVID-19 than do heterosexual individuals [19].…”
Section: Comparison With Other Studies and Discussing Important Differences In Resultsmentioning
confidence: 99%
“…33 Emerging research has documented LGBTQ + people's increased vulnerability to severe COVID-related outcomes based on their higher prevalence of comorbidities. 34 Elevated levels of existing mental health challenges among LGBTQ + individual's likely increases their vulnerability to pandemic-stress. [35][36][37] Preliminary studies suggest LGBTQ + people's health has been uniquely impacted by pandemic mitigation efforts, such that social distancing simultaneously shaped increases in alcohol use and reductions in LGBTQ + community connections and minority stress.…”
Section: Weight Change and Covid-19mentioning
confidence: 99%